Plants Under Stress: Exploring Physiological and Molecular Responses to Nitrogen and Phosphorus Deficiency - Swarup Mishra; Hannah Levengood; Jinping Fan; Cankui Zhang (Plants)
Nitrogen (N) and phosphorus (P) are essential mineral macronutrients critical for plant structure and function. Both contribute to processes ranging from cellular integrity to signal transduction. Since plants require these nutrients in high concentrations, replenishing them in soil often involves chemical fertilizers. However, the main source of P, rock phosphate, is non-renewable and in decline. N, second only to carbon, oxygen, and hydrogen in plant requirements, is vital for synthesizing proteins, nucleic acids, and plant pigments. Although N is available to plants through biological fixation or fertilizer application, the frequent application of N is not a sustainable solution due to environmental concerns like groundwater contamination and eutrophication. Plants have developed sophisticated mechanisms to adapt to nutrient deficiencies, such as changes in root architecture, local signaling, and long-distance signaling through the phloem. A dual deficiency of N and P is common in the field. In addition to individual N and P deficiency responses, this review also highlights some of the most recent discoveries in the responses of plants to the combined N and P deficiencies. Understanding the molecular and physiological responses in plants to mineral deficiency will help implement strategies to produce plants with high mineral use efficiency, leading to the reduced application of fertilizers, decreased mineral runoff, and improved environment.